Basic Concepts and General Framework of Public Administration Organization - Hulkó, Gábor (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
The organization of public administration has traditionally been considered an internal affair ofthe state. This chapter addresses some of the fundamental issues pertaining to the functioning and organization of public administration, offering a comprehensive overview over these topics. Subsequently, country studies are presented to deliver a comprehensive examination of the national regulatory issues pertaining to public administration law. The present text offers a general definition of the concept of public administration, a classification of some of its fundamental operational principles, and a description of the general issues pertaining to the systems of public administration. Particular emphasis is placed on the organizational issues and principles of central and territorial state administration, and on the organizational provision of certain aspects of public services. Additionally, the chapter includes a brief overview of self-governing systems, with specific attention to local and regional municipalities as the unique, autonomous intermediaries of state power in relation to citizens. KEYWORDS: public administration, state organization, principles of public administration, state administration, local self-governments Bibliography Balazs, I. (2013) ‘Az „Europai Kozigazgatasi Ter” es az europai kozigazgatasi jog’ in Lapsanszky, A. (ed.) Közigazgatási jog — Fejezetek szakigazgatásaink köréből (III. kötet). Budapest: Wolters Kluwer. Balazs, I., Bencsik, A., Bukodi, G., Csorgits, L., Fabian, A., Hoffman, I., Hulko, G., Ivancsics, I., Jozsa, Z., Karpati, O., Kurunczi, G., More, S., Pal, E., Rixer, A., Siket, J., Temesi, I., Varga, A., Balazs, I., Papp, O. (2014) Local self-Government in Hungary: Local Self-Governance in the Member States of European Union. Lille: OLA. Fabian, A., Hoffman, I. (2014) Az államigazgatási területi és helyi szervei: kormányhivatalok, járási intézmények. Budapest: NKE. Franczel, R. (2013) ‘The regulation of the Prime Minister by the Fundamental Law’, Jog, Állam, Politika, 2013(2), pp. 17–44. Gyurita, R., Hulko, G., Kalman, J., Toth, T. (2013) ‘Organisation of the Hungarian Public Administration’ in Smuk, P. (ed.) The Transformation of the Hungarian Legal System 2010-2013. Budapest: CompLex Wolters Kluwer, pp. 155–184. Gyurita, E. R., Hulko, G., Kalman, J., Kiraly, P. B., Lapsanszky, A. (2024) Általános közigazgatástan. Győr: Universitas-Győr Nonprofit Kft. Hulko, G., Kalman, J. (2013) ‘Autonom strukturak Magyarorszag es a Cseh Koztarsasag allamigazgatasaban’, Új Magyar Közigazgatás, 6(10), pp. 1–8. Hulko, G. (2013) ‘Organization of the Hungarian Public Administration: The system of local governments’ in Smuk, P. (ed.) The Transformation of the Hungarian Legal System 2010-2013. Budapest: CompLex Wolters Kluwer, pp. 171–184. Hulko, G. (2018) ‘A kozigazgatas fogalmanak meghatarozasa es műkodesenek alapvető jellemzői (I. Fejezet 1-5. pont)’ in Kalman, J., Lapsanszky, A. (eds.) Közigazgatási jogi alapismeretek. Győr: Universitas-Győr Nonprofit Kft, pp. 17–27. Hulko, G. (2024) ‘Administrative Law in Hungary’ in Deviatnikovaitė, I. (ed.) Comparative Administrative Law – Perspectives from Central and Eastern Europe. London: Routledge, pp. 36–67; https://doi.org/10.4324/9781003458135-2. Kalman, J., Lapsanszky, A. (eds.) (2017) Közigazgatási jogi alapismeretek. Győr: Universitas-Győr Nonprofit Kft. Koi, Gy. (2008) ‘Magyary Zoltan, mint az osszehasonlito kozigazgatas uttorő művelője’, Jogtudományi Közlöny, 63(7–8), pp. 352–360. Lapsanszky, A., Patyi, A., Takacs, A. (2017) A közigazgatás szervezete és szervezeti joga. Budapest: Dialog Campus. Lapsanszky, A., Patyi, A., Varga, Zs. A. (2024) A magyar közigazgatási jog általános tanai (bővített kiadás). Győr: Universitas-Győr Nonprofit Kft. Lőrincz, L. (2010) A közigazgatás alapintézményei. Budapest: HVG-Orac. Madarasz, T. (1989) A magyar államigazgatási jog alapjai. Budapest: Tankonyvkiado. Nagy, M. (2011) ‘A kozigazgatasi felelősseg — mi van a jogon tul?’ in Fazekas, M. (ed.) A közigazgatás tudományos vizsgálata egykor és ma: 80 éve jött létre a budapesti jogi karon a Magyar Közigazgatástudományi Intézet. Budapest: Gondolat Kiado.Pankucsi, M. (2014) ‘Civilekkel a civilekert — Az ellenzeki szerveződesektől a miniszteriumon at a Furmann alapitvanyokig’ in Simon, J. (ed.) Civil társadalom és érdekképviselet Közép-Európában. Budapest: L’Harmattan Kiado. Patyi, A. (2017) A közigazgatási működés jogi alapjai. Budapest: Dialog Campus Kiado. Patyi, A. (2019) ‘A kozigazgatas a magyar allam rendszereben’ in Orban, B., Szalai, (eds.) Ezer éve Európa közepén: A magyar állam karaktere. Budapest: Mathias Corvinus Collegium, Tihanyi Alapitvany, pp. 283–310. Patyi, A. (2022) ‘Issues of fundamental procedural rights and procedural constitutionality in the Fundamental Law’, Institutiones Administrationis – Journal of Administrative Sciences, 2(1), pp. 6–23 [Online]. Available at: https://doi. org/10.54201/iajas.v2i1.27 (Accessed: 12 February 2024). Patyi, A. (2024) ‘Nehany gondolat a kozigazgatasi feladatokrol es a funkciokrol’ in Kutasi, G. (ed.) Domi esse et in Europa et in mundo: Ünnepi tanulmányok a 70 éves Halmai Péter tiszteletére. Budapest: Ludovika Egyetemi Kiado, pp. 751–766. Patyi, A., Varga, Zs. A. (2012) Általános közigazgatási jog (az Alaptörvény rendszerében). Pecs-Budapest: Dialog Campus. Petretei, J. (2013) Constitutional Law of Hungary II. State Organization. Pecs: Kodifikator Alapitvany. Rixer, A. (2014) ‘Traditional features of Hungarian public administration’, Acta Universitatis Sapientiae, Legal Studies, 3(1), pp. 55–78. Rozsnyai, K. (2017) ‘A kozigazgatas fogalma’ in Fazekas, M. (ed.) Közigazgatási jog. Általános rész I. Budapest: ELTE Eotvos Kiado, pp. 21–35. Sladeček, V. (2019) Obecné správní parvo. 4th edn. Praha: C.H. Beck. Szalai, E. (2014) ‘A kozigazgatas műkodese, tevekenysegfajtai’ in Fazekas, M. (ed.) Közigazgatási jog. Általános rész I. Budapest: ELTE Eotvos Kiado, pp. 59–77. Szalai, E. (2017) ‘A kozigazgatasi jog helye a jogrendszerben’ in Fazekas, M. (ed.) Közigazgatási jog. Általános rész I. Budapest: ELTE Eotvos Kiado, pp. 21–30. Tamas, A. (1994) Public Administration Law I. Miskolc: JATEPress.